An Analysis of Sexual Comments on Social Media: Men’s Comments On Women’s Twitter Posts - Kurniawan, Rudy; Lionardo, Andries; Hardinanto, Eko; Sulton, Agus (KnE Social Sciences, 2023)
This research aimed to analyze the sexual comments made by men on women’s posts on Twitter. During the COVID-19 pandemic, there was an increase in the use of social media Twitter makes it easier for individuals to communicate with people they know and to interact with other users with minimal restrictions. Twitter allows its users to upload selfies and allows other users to comment on those pictures. This research analyzed sexual comments on @lucintaluna and @dododid selfies during 2021. The authors found three major themes in the comments using Norman Fairclough’s critical discourse analysis method. They were calling the women beautiful, objectifying the women and expressing stigmas and stereotypes. Through this research, the authors also found that online-based gender violence can be experienced by anyone in various forms. Keywords: Pandemic covid-19, Gender Violence, Social Media, Twitter, Critical Discourse Analysis